Adsorption Efficiency of Cement Impregnated Magnesium Oxide on the Removal of Fluoride - Umlong, Iohborlang M.; Das, Bodhaditya; Devi, Rashmi Rekha (Defence Life Science Journal, 2020)
Presence of fluoride in drinking water above the prescribed limit may lead to a severe health complication. We present in this paper the fluoride removal capacity of cement impregnated MgO (MgO-cement) from drinking water. MgO-cement was prepared by adding magnesium oxide (MgO) into the cement slurry solution in the ratio of 1:10. Batch experiments were performed as a function of adsorbent dose, contact time, effect of pH and effect of co-ions. The percentage removal decreases with increasing initial fluoride concentration. Co-ions effect revealed that hydroxide ion was found to interfere more with fluoride removal followed by bicarbonate and least effect with sulphate. Reaction mechanism follows Freundlich isotherms. From the kinetic study we observed that uptake of fluoride ion is fast in the first sixty minutes and equilibrium time found to be independent of the initial fluoride concentration. Adsorption kinetics followed the pseudo second order model showing that the sorption of fluoride is a complex process. Surface as well as intraparticle diffusion contribute in the sorption process. No leaching of magnesium in the treated water was detected.